Thirty-five Years of Long-run Energy Forecasting : Lessons for Climate Change Policy - Hourcade, Jean-Charles; Nadaud, Franck (2012)
This paper sheds light on an implicit dimension of the climate policy debate: the extent to which supply-side response (emission-reducing energy technologies) may substitute for the transformation of consumption behavior and thus help get around the political difficulties surrounding such behavioral transformation. The paper performs a meta-review of long-term energy forecasts since the end of the 1960s in order to put in perspective the controversies around technological optimism about the potential for cheap, large-scale, carbon-free energy production. This retrospective analysis encompasses 116 scenarios conducted over 36 years and analyzes their predictions for a) fossil fuels, b) nuclear energy, and c) renewable energy. The analysis demonstrates how the predicted relative shares of these three types of energy have evolved since 1970, for two cases: a) predicted shares in 2010, which shows how the initial outlooks for the 2000-2010 period have been revised as a function of observed trends; and b) predicted shares for t+30, which shows how these revisions have affected medium-term prospects. The analysis shows a decrease, since 1970, in technological optimism about switching away from fossil fuels; this decrease is unsurprisingly correlated with a decline in modelers beliefs in the suitability of nuclear energy. But, after a trend of increasing optimism, a declining trend also characterizes renewable energies in the 1980s and 1990s before a slight revival of technological optimism about renewables in the aftermath of Kyoto.